2021
DOI: 10.3390/pathogens10020179
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Multi-Locus Analysis of Giardia duodenalis in Coypus (Myocastor coypus) in China

Abstract: Giardia duodenalis is a major gastrointestinal parasite found globally in both humans and animals. This work examined the occurrence of G. duodenalis in coypus (Myocastor coypus) in China. Multi-locus analysis was conducted to evaluate the level of genetic variation and the potential zoonotic role of the isolates. In total, 308 fecal samples were collected from seven farms in China and subjected to PCR screening to reveal G. duodenalis. Notably, G. duodenalis was detected in 38 (12.3%) specimens from assemblag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Among them, assemblages A and B have a broad host range and commonly found in humans [55]. In fact, some recent studies in China also reported the occurrence of assemblage Ain pet chipmunks, coypus and pet chinchillas, while assemblage Bin bamboo rat, coypus and pet chinchillas [54][55][56][57]. These two assemblages detected in this study, suggesting that these two rodent species can play a role in the zoonotic dissemination of G. duodenalis.…”
Section: Author Contributionssupporting
confidence: 56%
See 2 more Smart Citations
“…Among them, assemblages A and B have a broad host range and commonly found in humans [55]. In fact, some recent studies in China also reported the occurrence of assemblage Ain pet chipmunks, coypus and pet chinchillas, while assemblage Bin bamboo rat, coypus and pet chinchillas [54][55][56][57]. These two assemblages detected in this study, suggesting that these two rodent species can play a role in the zoonotic dissemination of G. duodenalis.…”
Section: Author Contributionssupporting
confidence: 56%
“…China: house mouse (3.2%, 1/31); Asian house rat (6.1%, 2/33); brown rat (6.6%, 11/168 and 9.3%, 33/355); pet chipmunks (8.6%, 24/279); bamboo rat (10.8%, 52/480); coypus (12.3%, 38/308); pet chinchillas (27.1%, 38/140) [26,38,[54][55][56][57] (Table 3).…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this special issue also included molecular epidemiological studies directed to assess the occurrence, genetic diversity and zoonotic potential of Cryptosporidium spp. and G. duodenalis in pet dogs and cats [17], livestock [18], and farmed rabbits and rats [19][20][21], mostly in China.…”
mentioning
confidence: 99%
“…Some authors have interpreted all this information as evidence in support of considering C. hominis as a zoonotic species [45]. Regarding intensive animal farming, Cui et al [19] investigated the presence, molecular variability and zoonotic potential of G. duodenalis in coypus (n =308), reared in fur farms in six Chinese provinces/autonomous regions. The parasite was detected in all farms investigated at variable infection rates, ranging from 1-29%.…”
mentioning
confidence: 99%